Integrasi Sektor Perikanan Dan Pertanian Dalam Mendukung Ketahanan Pangan Dan Pembangunan Ekonomi Perdesaan - Nurafnikwati Telaumbanua; Dermawan Zebua (CV. SINAR HOWUHOWU, 2026)
The fisheries and agriculture sectors are two strategic sectors that play a vital role in supporting food security, employment, and rural economic development in Indonesia. Both serve not only as food providers but also as primary sources of income for the majority of rural communities. This study aims to analyze the role of integration between the fisheries and agriculture sectors in improving food security and community welfare. The research method used is a descriptive qualitative approach with literature review and secondary data analysis sourced from government reports, scientific publications, and national statistical data. The results show that integration of the fisheries and agriculture sectors, such as the rice-fish farming system and the utilization of agricultural waste for fish feed, can increase production efficiency, reduce operational costs, and provide added economic value for farmers and fishermen. However, implementing this integration still faces various obstacles, including technological limitations, limited access to capital, and minimal mentoring and outreach. Therefore, integrated and sustainable policies are needed to promote synergistic development of the fisheries and agriculture sectors.